Effect of Prolonged Use of Facemask on Ambulance Driver During Covid 19: A Questionnaires Study - Shweta A. Panchbudhe; Milind Kahile; Neha Deshmukh; Neha Chaudhary; Anjali Chiwhane; Saurabh Hadke (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The nose is a complex organ that shapes and has many roles as an integral part of the face.The nose’s primary purpose is to humidify, warm the inspired air, and also helps to remove the destructiveparticles from entering the lower respiratory tract. In general, an average adult inspires about 10,000 L ofair each day. Nasal mucosa is a highly vascular structure and has a large surface area of 150 cm square.Physiologically, the nose has 50% resistance in the entire airway, which when affected plays a significantrole in total respiratory function. that prolonged use of facemasks induces difficulty in breathing on exertionand excessive sweating around the mouth to the Ambulance driver which results in poorer adherence andincreased risk of susceptibility to infectionObjectives: The aim of this study is to determine the effects of prolonged usage of N95 respirators andsurgical facemasks on Ambulance driverMaterial and Methods: A self constructed questionnaire containing 10 questions regarding the prolongeduse of N95 respirators and surgical mask on Ambulance driver between the age group of 35 – 50 years werehanded to themResults: This study suggests that prolonged use of facemasks induces difficulty in breathing on exertionand excessive sweating around the mouth to the Ambulance driver which results in poorer adherence andincreased risk of susceptibility to infection.